Measuring and assessing impacts of Fair Trade USA on farm workers in Nicaragua - Mosquera Echeverry, Erika Eliana; Río Duque, Martha Lilia del (2015)
After the first year of the research project “Measuring and Assessing Impacts of Fair Trade for All on farmers, farmworkers and the overall fair trade Market System” we made infographics with the quantitative data collected of the baseline conditions in three of the four countries in which our research is located: Peru, Nicaragua and Honduras. The infographics summarize the current status of the four Fair Trade Principles: Empowerment, economic development, social responsibility, and environmental stewardship of the independent small producers and farm workers with the certification compared with non-certified small producers and farm workers.